The Disease Delusion : CONQUERING THE CAUSES OF CHRONIC ILLNESS FOR A HEALTHIER, LONGER, AND HAPPIER LIFE - Bland, Jeffrey, (HARPER WAVE, 2014)
A biochemist and pioneer in naturopathic medicine introduces the concept of functional medicine, discussing the reasons for a host of ailments and offering achievable, science-based solutions that can alleviate chronic illness.